Expanding the BP1-BP2 15q11.2 Microdeletion Phenotype: Tracheoesophageal Fistula and Congenital Cataracts - D. Wong; S. M. Johnson; D. Young; L. Iwamoto; S. Sood; T. P. Slavin (Case Reports in Genetics)
The proximal q arm of chromosome 15 contains breakpoint regions BP1–BP5 with the classic deletion of BP1–BP3 best known to be associated with Prader-Willi and Angelman syndromes. The region is approximately 500 kb and microdeletions within the BP1-BP2 region have been reported in patients with developmental delay, behavioral abnormalities, and motor apraxia as well as dysmorphic features including hypertelorism, cleft or narrow palate, ear abnormalities, and recurrent upper airway infections. We report two patients with unique, never-before-reported 15q11.2 BP1-2 microdeletion syndrome findings, one with proximal esophageal atresia and distal tracheoesophageal fistula (type C) and one with congenital cataracts. Cataracts have been described in Prader-Willi syndrome but we could not find any description of cataracts in Angelman syndrome. Esophageal atresia and tracheoesophageal fistula have not been reported to our knowledge in either syndrome. A chance exists that both cases are sporadic birth defects; however, the findings of the concomitant microdeletion cannot be overlooked as a possible cause. Based on our review of the literature and the presentation of our patients, we recommend that esophageal atresia and distal tracheoesophageal fistula as well as congenital cataracts be included in the phenotypic spectrum of 15q11.2 BP1-2 microdeletion syndrome.